Internal Report: Action Planning and Network Consolidation of the Disruptive Seeds Network in Kenya - Bell, Shavon; Ratner, Blake; Kimani, Martin Njoroge; Rutting, Lucas; Veeger, Marieke; von Breymann, Randolph (Bioversity International and the International Center for Tropical Agriculture, 2024)
Brought together by the CGIAR Climate Resilience Initiative under the banner of the Disruptive Seeds process, the emerging Kenyan Disruptive Seeds coalition was first convened in September 2024. Over the course of an initial three-day workshop, selected organizations developed transformation pathways for durable systems change to bring about a more just and sustainable food system in Kenya.